Evaluating critical element that influence technology transfer success: A study on electric and electronic in manufacturing in Malaysia - Abdul Halim, Haliza Azura; Ibrahim, Amlus; T., Ramayah (2010)
This study discussed and determines the success factors that influence technology transfer process at Malaysia. “Many do not understand that the technology transfer process involves a long period of time before reaching a successful commercialization stage.Many of the successes that we are seeing today are as a result of ideas that came out in the 1970’s,” explained Mr Jon Sandelin, Senior Associate Emeritus, Technology Transfer Office, Stanford University, USA.As illustrated by the students of the technology transfer design project team, during recent years, technology transfer has become an important issue to the major space faring countries and space agencies. Reasons for this are increasing global economic competition, decreasing national budgets for space research and activities, and increasing concern from the public to justify government space expenditures.Furthermore technology transfer is identified as a process to get the highest possible value out of the government funding. An idealistic goal of technology transfer could be that the space sector finances itself independently by transferring space technologies to other fields of applications for commercialization.An objective of technology transfer is to seek the widest possible applications and utilization of space technology by the non-space industry.There are a more problems occur in technology transfer.Transfer the technology from one place to another place can create problem like problems in culture, research and development, Geographical location and environmental factors. Technology does not stand alone, but encompasses political, social, economic, and cultural values that can serve as barriers to the diffusion or transfer of technology.These barriers exist for all innovations, this study try to answer the following issues, What is the relationships of culture towards technology transfer success?, what is the relationships between research and development in manufacturing companies towards technology transfer success?, what is the relationships of geographical location towards technology transfer success?, lastly what is the relationships between physical environments towards technology transfer success?.We will carry out hypothesis testing using SPSS. Sample for this study will be selected from directory of Federal Manufacturing of Malaysia (FMM). This study will give significant impact toward manufacturer in implementing technology transfer process.